Paleoecology, biochronology, and paleobiogeography of Eurasian Rhinocerotidae during the Early Pleistocene: The contribution of the fossil material from Dmanisi (Georgia, Southern Caucasus). Issue 156 (July 2021) - Pandolfi, Luca; Bartolini-Lucenti, Saverio; Cirilli, Omar; Bukhsianidze, Maia; Lordkipanidze, David; Rook, Lorenzo
Abstract: Rhinocerotidae represents a common element in the Eurasian Pleistocene faunas. Origin, dispersal route, and biochronology of several species are still poorly understood due to gaps in the fossil record, in particular from central Eurasia. A remarkable collection of rhinoceros remains was recovered from the Early Pleistocene site of Dmanisi (Georgia). This collection is unique for the Early Pleistocene Rhinocerotidae records due to its abundance in remains, its age (ca 1.8 Ma) and geographic position (between Eastern and Western Eurasia). Two crania, which display some different morphological traits, are assigned to two different morphotypes and investigated by means of geometric morphometrics using landmarks and semilandmarks. Shapes in lateral and dorsal views of different Rhinocerotini species are compared with the studied crania to infer paleoecological information. The shape in the lateral view reflects ecological niche, in particular feeding type from browsing to grazing, and it also represent taxonomic discrimination. Morphotypes 1 and 2 from Dmanisi fall in two different clusters, corresponding to two different species, notably in lateral view. The results suggest a niche partitioning during the Early Pleistocene of Dmanisi between a browse-dominated and a grass-dominated mixed feeders, or possibly the presence of two ecomorphotypes of the same species. A comprehensive update of the Early Pleistocene occurrences of Eurasian Rhinocerotidae is reported in the discussion on the paleoecology of the extinct Northern Eurasian rhinocerotines.